Aqua(2,2 `-bipyridine-kappa(2) N,N `)(3,5-dinitrobenzoato-kappa O-1)copper(II) tetrahydrofuran monosolvate - Abdullah, N.; Mohamadin, M.I.; Safwan, A.P.; Tiekink, E.R.T. (International Union of Crystallography, 2010)
The title complex, [Cu(C7H3N2O6)(2)(C10H8N2)(H2O)]center dot C4H8O, features a pentacoordinate Cu-II atom bound by two monodentate carboxylate ligands, a bidentate 2,2 `-bipyridine molecule [dihedral angle between pyridine rings = 5.0 (2)degrees]and a water molecule. The resulting N2O3 donor set defines a distorted square-pyramidal geometry with the coordinated water molecule in the apical position. In the crystal, the presence of O-H-w center dot center dot center dot O-c (w = water and c = carbonyl) hydrogen bonding leads to the formation of a supramolecular chain propagating along the c axis, which associates into a double chain via C-H-w center dot center dot center dot O-c and pi-pi contacts between pyridyl rings [centroid-centroid distance = 3.527 (3) angstrom]. The solvent molecules, which are disordered over two orientations in a 0.678 (11):0.322 (11) ratio, occupy voids defined by the complex molecules and are held in place via C-H center dot center dot center dot O interactions.